The Effects of Job Characteristics and Job Satisfaction on Work Performance With Employee Engagement as Mediator for Generation Y in The Indonesia Oil and Gas Industry - Widiati Widiati (Universitas Muhammadiyah Enrekang, 2023)
Fossil energy still plays as the main energy source in daily activities. The government of the Republic of Indonesia set a target to reach 1 million BOPD and 12 BSCFD in the year 2030 as part of strategic plan 4.0 which very challenging target for the oil and gas player in Indonesia. 55% of the total workforce in the upstream oil and gas in Indonesia are Gen Y and they intend to quit their job if there is any uncomfortable things happened (Arora & Dhole, 2019). This will be a challenge for HR management to retain talent in the upstream oil and gas industry. The questionnaire, designed as a self-reported survey, was distributed to employees of the Oil and Gas Industry. Data processing uses SEM Methodology. It tests 300 respondence by using a data questionnaire. It test 300 respondence by using a data questionnaire and Lisrel 8.8 was used to analyze the data. The finding proposes the positive effect between Job Characteristics, Job Satisfaction, Employee Engagement, and Job Performance. The positive effect was also found on Employee Engagement as the mediator amid Job Characteristics, Job Satisfaction, and Job Performance. This paper will provide reference and practical benefits for Human Management to support the achievement of oil & gas strategic plan 4.0 in 2023.